2017
DOI: 10.1002/anie.201701162
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Fluorosulfonylvinylation of Organic Iodides

Abstract: A palladium-catalyzed fluorosulfonylvinylation reaction of organic iodides is described. Catalytic Pd(OAc)2 with stoichiometric silver(I) trifluoroacetate enables the coupling process between an (hetero)aryl or alkenyl iodide and ethenesulfonyl fluoride (ESF, 1). The method is demonstrated in the successful syntheses of eighty-eight otherwise difficult to access compounds in up to 99% yields, including the unprecedented 2-heteroarylethenesulfonyl fluorides, and 1,3-dienylsulfonyl fluorides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…The products 52 proved to be selectively addressable bis-electrophiles for sulfur(VI) fluoride exchange (SuFEx) click chemistry, in which either the alkenyl moiety or the sulfonyl fluoride group could be exclusively attacked by nucleophiles under defined conditions, making these simple cores attractive for covalent drug discovery [60]. Later, Qin and Sharpless employed a similar strategy for the synthesis of 2-(hetero)arylethenesulfonylfluorides (54) and 1,3-dienylsulfonyl fluorides (56) (Scheme 9) [61]. They found that a combination of catalytic Pd(OAc)2 with a stoichiometric amount of silver(I) trifluoroacetate enabled the coupling process between either an (hetero)aryl or alkenyl iodide (53 or 55) and ethenesulfonyl fluoride (ESF, 51).…”
Section: Fluorine-containing Vinyl Sulfur Compounds As the Cross-coupmentioning
confidence: 99%
See 4 more Smart Citations
“…The products 52 proved to be selectively addressable bis-electrophiles for sulfur(VI) fluoride exchange (SuFEx) click chemistry, in which either the alkenyl moiety or the sulfonyl fluoride group could be exclusively attacked by nucleophiles under defined conditions, making these simple cores attractive for covalent drug discovery [60]. Later, Qin and Sharpless employed a similar strategy for the synthesis of 2-(hetero)arylethenesulfonylfluorides (54) and 1,3-dienylsulfonyl fluorides (56) (Scheme 9) [61]. They found that a combination of catalytic Pd(OAc)2 with a stoichiometric amount of silver(I) trifluoroacetate enabled the coupling process between either an (hetero)aryl or alkenyl iodide (53 or 55) and ethenesulfonyl fluoride (ESF, 51).…”
Section: Fluorine-containing Vinyl Sulfur Compounds As the Cross-coupmentioning
confidence: 99%
“…They found that a combination of catalytic Pd(OAc)2 with a stoichiometric amount of silver(I) trifluoroacetate enabled the coupling process between either an (hetero)aryl or alkenyl iodide (53 or 55) and ethenesulfonyl fluoride (ESF, 51). The reaction was demonstrated in the successful synthesis Later, Qin and Sharpless employed a similar strategy for the synthesis of 2-(hetero)arylethenesulfonylfluorides (54) and 1,3-dienylsulfonyl fluorides (56) (Scheme 9) [61]. They found that a combination of catalytic Pd(OAc) 2 with a stoichiometric amount of silver(I) trifluoroacetate enabled the coupling process between either an (hetero)aryl or alkenyl iodide (53 or 55) and ethenesulfonyl fluoride (ESF, 51).…”
Section: Fluorine-containing Vinyl Sulfur Compounds As the Cross-coupmentioning
confidence: 99%
See 3 more Smart Citations